Humboldt Lab Tanzania - Reyels, Lili; Ivanov, Paola; Weber-Sinn, Kristin (2018)
Numerous objects are kept in the storages of the Ethnologisches Museum, Berlin that were plundered from what was then known as German East Africa during the German colonial period of 1886-1918, for instance, during the Maji Maji War. In the project ""Humboldt Lab Tanzania"" Tanzanian and German academics, curators and artists take a critical look at selected artefacts, among them a large Swahili drum, objects of healing and a talisman. With the Ethnologisches Museum's imminent move to the Humboldt Forum, the collections from the former German colonies and their often-problematic provenance have again come under the focus of public awareness. The project participants from Germany and Tanzania test out new ethnological, historical and museological approaches to this shared ""colonial legacy"". The focus will be on the role and significance of the objects in the past and today as well as on the question of how to deal with ethnological collections from colonial contexts: In which way these sensitive objects and their histories can be (re)presented ? Where is the appropriate location for these objects? How can cooperation be shaped? And which new perspectives are being opened by a joint provenance research? Texte des gesamten Buches sind dreisprachig in Deutsch, Englisch und Kiswahili.